Destitution: A Discourse' - Sen, Amartya; Robinson, James (Journal of Economic Literature, 2016)
T WO HUNDRED and seventeen years after Adam Smith's publication, An Inquiry Into Wealth of Nations, comes Partha Dasgupta's An Inquiry into Well-Being and Destitution, which apparently is intended to be equally broad-ranging. Smith identified two forces that regulated level of per caput consumption in any nation, first being the skill, dexterity and judgment with which its labor is generally applied, and second being the proportion between number of those who employed in useful labour and that of those who not so employed. He distinguished sharply between savage nations of hunters and fishers from civilized and thriving nations. Although in former every individual who is able to work is more or less employed in useful labour, most are so miserably poor, that from mere want, they frequently reduced, or, at least, think themselves reduced, to necessity of sometimes destroying and sometimes of abandoning their infants, their old people, and those afflicted with lingering diseases, to perish with hunger or to be devoured by wild beasts (Smith 1937, pp. lviilviii). In contrast, in latter nations,